2016
DOI: 10.1038/nrrheum.2016.191
|View full text |Cite
|
Sign up to set email alerts
|

Extent and patterns of off-label use of rituximab for SLE

Abstract: Despite conflicting evidence from clinical trials, rituximab continues to be used off-label in the treatment of systemic lupus erythematosus (SLE). A new study has now investigated the use of this drug for SLE in Europe, including indications for use and patient characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…The identification of a population of atypical memory T-bet + CD11c + B cells in patients with SLE raises the possibility that targeting this population may open new therapeutic opportunities for this complex disease, as the efficacies of B cell depletion therapy by targeting whole B cells in patients with SLE are highly variable 1 22. Particularly, it was reported that an expanded population of CD19 hi AtMs in patients with SLE predicts a poor clinical response to rituximab treatment 8.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of a population of atypical memory T-bet + CD11c + B cells in patients with SLE raises the possibility that targeting this population may open new therapeutic opportunities for this complex disease, as the efficacies of B cell depletion therapy by targeting whole B cells in patients with SLE are highly variable 1 22. Particularly, it was reported that an expanded population of CD19 hi AtMs in patients with SLE predicts a poor clinical response to rituximab treatment 8.…”
Section: Introductionmentioning
confidence: 99%
“…РТМ широко и с большим успехом используется при СКВ в клинической практике [108] и включен в международные [109][110][111][112][113] рое вошли пациенты с активной СКВ без поражения почек, и LUNAR (Lupus Nephritis Assesment with Rituximab) [116] -с волчаночным нефритом (ВН), «первичные конечные точки», отражающие эффективность терапии, достигнуты не были (табл. 7).…”
Section: системные васкулитыunclassified
“…While some B cell-targeting therapies generate promising results, the efficacies of certain trials are variable, indicating a highly heterogeneous feature of the B-cell compartment in SLE. 1,6,7 B-cell aberrations in SLE are reflected in multiple aspects. Transitional B (Btr) cells and plasmablasts are greatly expanded while IgM + memory B cells are decreased in active SLE patients.…”
Section: Introductionmentioning
confidence: 99%